2003
DOI: 10.1073/pnas.1534875100
|View full text |Cite
|
Sign up to set email alerts
|

Coastal oceanography sets the pace of rocky intertidal community dynamics

Abstract: The structure of ecological communities reflects a tension among forces that alter populations. Marine ecologists previously emphasized control by locally operating forces (predation, competition, and disturbance), but newer studies suggest that inputs from large-scale oceanographically modulated subsidies (nutrients, particulates, and propagules) can strongly influence community structure and dynamics. On New Zealand rocky shores, the magnitude of such subsidies differs profoundly between contrasting oceanogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
233
3
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(258 citation statements)
references
References 29 publications
17
233
3
5
Order By: Relevance
“…The supply of larvae establishes the densities of communities, while the supply of zooplankton determines the food supply for growth and reproduction of filter-feeding foundation species of rocky shore communities [3,35,36]. In turn, these subsidies determine the intensity of top -down processes in communities [4,37]. Hence, surfzone hydrodynamics as well as near-shore productivity may determine the initial abundance of communities that are later modified by top-down processes, physiological stress and disturbance [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply of larvae establishes the densities of communities, while the supply of zooplankton determines the food supply for growth and reproduction of filter-feeding foundation species of rocky shore communities [3,35,36]. In turn, these subsidies determine the intensity of top -down processes in communities [4,37]. Hence, surfzone hydrodynamics as well as near-shore productivity may determine the initial abundance of communities that are later modified by top-down processes, physiological stress and disturbance [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alongshore variation in surfzone hydrodynamics was proposed to affect the recruitment of larvae to rocky intertidal populations in time and space, thereby affecting the intensity of postsettlement interactions among members of intertidal communities [7,8]. If so, spatial variation in surfzone hydrodynamics also may affect the concentration of entire plankton communities that provide food subsidies for suspension-feeding invertebrates, including foundation species that form habitat for many other species [3,4]. We previously demonstrated that the densities of barnacle and limpet recruits were greater onshore of dissipative than reflective surf zones [8].…”
Section: Introductionmentioning
confidence: 99%
“…After decades of focusing on top-down (i.e., consumer-driven) effects on population and community dynamics, ecologists recognize that top-down and bottom-up (i.e., variation in nutrients and productivity) mechanisms act in concert to regulate ecological systems (18)(19)(20)(21). Nonetheless, empirical examples of bottom-up effects on marine populations and communities are relatively rare, in part because of the difficulty of manipulating potential factors on the appropriate spatial and temporal scales (3,20).…”
mentioning
confidence: 99%
“…The strength and nature of biological interactions (such as competition, herbivory and predation) vary as a function of many factors (e.g. abiotic conditions, population densities and the genetic make-up of species; Thompson & Cunningham 2002, Menge et al 2003. These moderating processes of species interactions are themselves variable across large spatial scales, such as latitudinal gradients, and at more local scales (Crowe et al 2013, Doxford et al 2013.…”
Section: Introductionmentioning
confidence: 99%